Survey Study about the Association between (Epstein Barr Virus) (EBV) Infection and Breast Cancer Attending Al-Sadder Teaching Hospital in Al-Najaf Al-Ashraf during Years 2017 - Ali Abdul Razak Al-Saegh (Journal of Global Pharma Technology, 2019)
This study was conducted in from January to December 2017, located was doing in Al-Sadder Teaching Hospital in Al-Najaf Al-Ashraf, to detect the relationship between the breast cancer and the EBV which causes cancer, total female attending to the Teaching Hospital is 16 cases the average age was between 31-64 years. Clinical symptom and X-ray was examined at first, Biopsy was doing and sent to the Department of Analysis technique Al-kafeel University for Histopathological and immunohistochemical examination. The aim of this study was to determine where there are associated between EBV and female breast cancer, be that breast malignancy risks in patients testing positive for EBV in Al-Najaf governor for the first time.